Conversion between Arbitrary Amplitude, Phase, and Polarization with Minimal Degrees of Freedom of Metasurface. Issue 2 (13th December 2021) - Bao, Yanjun; Weng, Qiang; Li, Baojun
Abstract: Metasurfaces are ultrathin optical elements that can manipulate the light at subwavelength scale. The light input on the metasurface can be converted into output with abrupt changes of amplitude, phase, and polarization (APP) properties. However, a simultaneous and arbitrary conversion of all the three optical properties is not yet realized. In this paper, a Jones matrix with minimal number of four degrees of freedom that enables the conversion between two optical states with arbitrary APP distributions is proposed. The Jones matrix is constructed with a dielectric metasurface and is experimentally verified for various conversions of the three optical properties. This work unlocks some unknown powerful abilities of metasurface even with the minimal design degree of freedom, which can expand the scope of meta optics. Abstract : A dielectric metasurface with minimal number of four degrees of freedom of Jones matrix is proposed and experimentally demonstrated to enable the conversion between two optical states with arbitrary amplitude, phase, and polarization distributions. The results unlock some unknown powerful abilities of metasurface that can expand the scope of meta optics.